Physical Education and Sport: A Path to Inclusiveness, Equality and Sustainable Development - Gianpiero Greco; Luca Poli; Alessandro Petrelli; Francesco Fischetti; Stefania Cataldi (Pensa MultiMedia, 2024)
The purpose of the review was to (i) explore the social and cultural significance of physical education (PE) and its role in bridging sports and education, (ii) analyze the international historical context and educational policies to understand how PE and sports have evolved over time in terms of their role and importance, (iii) examine the inclusive role of PE and sports, demonstrating how they can contribute to promoting a fairer, more accessible, and sustainable environment. After an analysis of the literature using the Scopus and WoS databases on the global historical path of PE and sports, attention focused on some key principles related to Agenda 2030 and Sustainable Development Goals. Subsequently, the educational and inclusive value of these disciplines was further examined, considered as catalysts for inclusivity in the educational context. Through movement and bodily interaction, PE and sports not only foster individual growth but also stimulate active participation of everyone, embracing diversity and promoting an inclusive approach. Finally, the importance of lifelong learning was investigated as a fundamental objective of individual and social development together with PE and sports, which, through their approach focused on achieving transversal pedagogical objectives, can significantly contribute to a fundamental educational, inclusive, and sustainable path for the individual and the community.